1994
DOI: 10.2134/agronj1994.00021962008600050028x
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Legume and Fertilizer Nitrogen‐15 in a Long‐Term Cropping Systems Experiment

Abstract: iRelying more on biological N~ fixation has been suggested as a way to meet one of the major challenges of agricultural sustainability. A study was conducted to compare the fate of applied legume and fertilizer N in a long-term cropping systems experiment. Nitrogen-15-1abeled red clover (Trifolium pratense L.) and (NH4)2SO4 were applied microplots within the low-input and conventional cropping systems of the Farming Systems Trial at the Rodale Institute Research Center in Pennsylvania. The ~SN was applied to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
77
1
16

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(106 citation statements)
references
References 20 publications
12
77
1
16
Order By: Relevance
“…Deste modo, possivelmente, a maior porção do N remanescente, principalmente das culturas de cobertura, deve ter permanecido no solo dentro da zona explorada pelas raízes do milho, a exemplo do verificado por Azam et al (1985), para N de culturas de cobertura, e de Coelho et al (1991), para o N da uréia. A maior recuperação no solo do N oriundo de fontes orgânicas é bastante citada na literatura, encontrando-se entre 44 e 89 % do N para adubos verdes, e entre 12 e 53 % para fertilizantes minerais (Azam et al, 1985;Harris & Hesterman, 1990;Harris et al, 1994;Scivittaro et al, 2003), o que se deve, em parte, à maior absorção do N de fontes minerais pela planta em curto prazo (Ladd & Amato, 1986).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Deste modo, possivelmente, a maior porção do N remanescente, principalmente das culturas de cobertura, deve ter permanecido no solo dentro da zona explorada pelas raízes do milho, a exemplo do verificado por Azam et al (1985), para N de culturas de cobertura, e de Coelho et al (1991), para o N da uréia. A maior recuperação no solo do N oriundo de fontes orgânicas é bastante citada na literatura, encontrando-se entre 44 e 89 % do N para adubos verdes, e entre 12 e 53 % para fertilizantes minerais (Azam et al, 1985;Harris & Hesterman, 1990;Harris et al, 1994;Scivittaro et al, 2003), o que se deve, em parte, à maior absorção do N de fontes minerais pela planta em curto prazo (Ladd & Amato, 1986).…”
Section: Resultsunclassified
“…Ladd et al (1983) encontraram, também, valores menores do que 5 % de recuperação do N de leguminosas pelo trigo no segundo cultivo. O baixo aproveitamento do N pelo milho no ano agrícola subseqüente deve-se, provavelmente, ao fato de o N remanescente das culturas de cobertura e do fertilizante mineral ser encontrado, predominantemente, sob a forma de compostos orgânicos e sua disponibilidade seguir o padrão de mineralização da MOS (Harris et al, 1994). Por esta razão, o aproveitamento por cultivos subseqüentes é, em geral, bastante pequeno, da ordem de 1 a 6 % do montante aplicado (Harris & Hesterman, 1990;Scivittaro et al, 2000).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…These results indicated that the use efficiency of ryegrass green manure N was lower. Some studies suggested that organic N from crop residue or manure showed lower N use efficiency than mineral N fertilizers (Harris et al, 1994;Glendining et al, 1997Glendining et al, , 2001Kramer et al, 2002).…”
Section: Grain Yield and 15 N Uptake Of Upland Ricementioning
confidence: 99%
“…The value obtained is the legume fertiliser N replacement value. These N credits were found to be overestimated (Lory et al 1995) because legumes in rotation not only supply N (Ladd and Amato 1986;Janzen et al 1990;Harris et al 1994;Hossain et al 1996), but can also result in non-nutritional effects on the main crop (Janzen and Schaalje 1992;Stevenson and van Kessel 1996). Evidence suggests that underseeded legume can also affect cereal yields other than by simple contribution through improved N nutrition; competition for light, water and nutrients, reduction of weeds and diseases etc.…”
mentioning
confidence: 99%